The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0167560
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Modern Contraceptive Use in Kinshasa, DRC

Abstract: Recent research from Kinshasa, DRC, has shown that only one in five married women uses modern contraception; over one quarter have an unmet need for family planning; and almost 400 health facilities across Kinshasa report that they provide modern contraception. This study addresses the question: with reasonable physical access and relatively high unmet need, why is modern contraceptive prevalence so low? To this end, the research team conducted 6 focus groups of women (non-users of any method, users of traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 12 publications
5
65
4
Order By: Relevance
“…In addition to communication issues and differing spousal perspectives, cultural norms that support large families were revealed as a major barrier in a qualitative study conducted in Kinshasa with similar objectives. Although cultural norms were identified as contributing to non-use in this study undertaken in DRC rural areas, some women revealed that if their husband supported the use of a modern family planning method, they felt justified in using one, even if their family or friends criticised this decision (Muanda et al 2016). This finding differs from the common impression backed up by other studies that report that deep-rooted cultural beliefs about gender norms help explain non-use in rural areas (Farmer et al 2015).…”
Section: Discussioncontrasting
confidence: 95%
“…In addition to communication issues and differing spousal perspectives, cultural norms that support large families were revealed as a major barrier in a qualitative study conducted in Kinshasa with similar objectives. Although cultural norms were identified as contributing to non-use in this study undertaken in DRC rural areas, some women revealed that if their husband supported the use of a modern family planning method, they felt justified in using one, even if their family or friends criticised this decision (Muanda et al 2016). This finding differs from the common impression backed up by other studies that report that deep-rooted cultural beliefs about gender norms help explain non-use in rural areas (Farmer et al 2015).…”
Section: Discussioncontrasting
confidence: 95%
“…We discuss several probable explanations that could explain our results. lack of knowledge about types and sources of contraceptives was among the reasons for not using contraceptive methods [42]. Another study conducted in Chad found that a correlation exists between wealth and the knowledge about the family planning service providers.…”
Section: Discussionmentioning
confidence: 99%
“…Women may also not use specific services despite the availability and quality of services if they do not intend to use modern contraception. Strong social norms that support large families are among the reasons cited as barriers to modern contraceptive use in Kinshasa [42]. These norms also might be a strong barrier for some women to use modern contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…Better-educated women were more likely to practice contraception and to use modern methods (Bader, 2015). Data from the countries where the Demographic and Health Surveys have been conducted demonstrate the positive relationship between education and the use of family planning (Muanda, et al, 2016). Ochako, et al, (2017) analyzed the world fertility survey that was collected from 25 countries and found a positive relationship between women's education and the contraceptive method practices, and that education was associated with increased awareness, acceptability and use of contraception.…”
Section: Educationmentioning
confidence: 99%